The Impact of the Corona Pandemic on Retail in Inner Cities - Henry Goecke; Christian Rusche (Wirtschaftsdienst)
Abstract The coronavirus pandemic affects all sectors of the economy. The sector hardest hit by closures, restrictions and a changing consumer behavior is the inner-city retail. In fact, the frequency of passers-by and, therefore, potential customers in selected cities declined dramatically. The statistical sales figures that also include online retail and food retailers do not adequately represent the negative effects. A closer look at inner-city retail areas reveals that despite increased use of e-commerce channels, sales are still below the pre-corona level. Also, some areas of inner-city retail benefit, while others have lost dramatically. Therefore, triggered business failures can negatively affect the attractiveness of downtown as a whole and correspondingly, the areas that have been able to master the crisis in inner cities will also lose customers and turnover.